Chronic Stress, Genetic Risk, and Obesity in US Hispanic/Latinos: Results From the Hispanic Community Health Study/Study of Latinos. Issue 7 (5th July 2022) - Isasi, Carmen R.; Moon, Jee-Young; Gallo, Linda C.; Qi, Qibin; Wang, Tao; Sotres-Alvarez, Daniela; Llabre, Maria M.; Khambaty, Tasneem; Daviglus, Martha; Estrella, Mayra L.; Cai, Jianwen; Kaplan, Robert
ABSTRACT: Objective: This study aimed to investigate whether the association of chronic stress with obesity is independent of genetic risk and test whether it varies by the underlying genetic risk. Methods: The analysis included data from the Hispanic Community Health Study/Study of Latinos, a community-based study of Hispanic/Latinos living in four US communities (Bronx, NY; Chicago, IL; Miami, FL; San Diego, CA). The sample consisted of 5336 women and 3231 men who attended the Hispanic Community Health Study/Study of Latinos second in-person examination, had measures of obesity, and chronic stress, and were genotyped. Chronic stress burden was assessed by an eight-item scale. An overall polygenic risk score was calculated based on the summary statistics from GIANT and UK BioBank meta-analysis of body mass index (BMI) genome-wide association studies. Mixed-effect models were used to account for genetic relatedness and sampling design, as well as to adjust for potential confounders. Results: A higher number of chronic stressors were associated with both BMI ( β [log odds] = 0.31 [95% confidence interval = 0.23–0.38]) and obesity ( β [log odds] = 0.10 [95% confidence interval = 0.07–0.13]), after adjustment for covariates and genetic risk. No interactions were found between chronic stress and the genetic risk score for BMI or obesity. Conclusions: We did not find evidence for an interaction between chronic stress and polygenic risk score, which was not consistent with other publications that showed greater BMI or obesity in the groups with high stressors and elevated genetic risk.